The scientific thought in the holy Qur’an: an overview on mathematical data - Shogar, Ibrahim (IIUM Press, 2015)
In the twenty first century everybody should have ability to think scientifically. Such a capability enables the human intellect to deal properly with Nature and Revelation as the two major sources of knowledge and guidance. Revelation contains Divine guidance for development of human soul, while Nature contains patterns of laws which are essential for development of human intellect. This paper investigates the mathematical data in the holy Qur`an, and attempts to answer how the holy Qur`an inspires the scientific thinking through formation of mathematical mind and development of abstract concepts. For this purpose, the paper presents the basic mathematical sciences in the holy Qur`an. The paper is not concerned with history of science, nor the other modes of mathematical research in holy Qur`an, such as that which known as mathematical miracles; instead the paper presents the major classifications of mathematical sciences in the holy Qur`an, with focus on number theory and Algebra as inspired by the holy Qur`an through the Islamic inheritance system (`ilm al-Faraid). The method adopted in this paper is simple in nature, aiming at achieving three major goals: first, to shift the attention of modern mathematicians to the great mathematical data in the holy Qur`an, especially in the inheritance system, for their further study and analysis. Secondly, to expose non-mathematicians to the general content and the major classifications of mathematical science, as exhibited by the holy Qur`an. Third, role of the abstract knowledge and systematic mind in promotion of scientific research.